PENENTUAN LOKASI TEMPAT PENGOLAHAN AKHIR (TPA) SAMPAH KOTA BANJARBARU MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) - Andy Mizwar (EnviroScienteae, 2012)
The research was conducted in the District Cempaka, Banjarbaru, South Kalimantan, with the aim to determining the location of municipal solid waste landfill using Geographic Information Systems (GIS). In this study, the determination of landfill location carried out in three stages of assessment based on SNI 03-3241-1994. First phase (region feasibility) is done with a binary method to determine the feasibility zone as landfill sites based on eight criteria, namely: slope, geological conditions, distance to water bodies, proximity to residential areas, distance to the areas of agricultural cultivation, distance to protected areas, the distance to the airport, and proximity to the border area. Second phase (screen feasibility) performed by the method of Analytical Hierarchy Process (AHP) and Weighted Linear Combination (WLC) to determine the level of suitability of several alternative locations which have been obtained in the first stage of the assessment is based on seven criteria, namely: land area, buffer zone , soil permeability, groundwater depth, the intensity of rains, floods and transportation of garbage. Third phase (recommendation feasibility) to determine the best location of several alternative locations which have been obtained in previous assessments. GIS analysis is used to evaluate each of these evaluation criteria are spatially. Based on the results of the first and the second phase is known that there are 7 locations that are included in the category zone as a landfill with a decent level of fitness is included in the category of being and a total area of ± 403.448 ha or 2.75% of the Cempaka District. While based on the results of the third phase is known that only one location that could be recommended to become landfill site for Banjarbaru City.